CONDITION MONITORING OF ADDITIVE MANUFACTURING PROCESS USING SENSOR TECHNOLOGY - AIZATUL FARZANA, SALIM
Additive Manufacturing such as Fused Deposition Modeling is a new and promising manufacturing process in the industry. Failure of a printing process can cause losses, waste, and potential damage to the machine and product. Hence, this study was carried out to investigate method that detect Fused Deposition Modeling machine failure. In this study, a system applying sensor technology to monitor Fused Deposition Modeling machine for process condition monitoring was developed. This study began with designing and developing the vibration detection system using Arduino and installation of the Arduino-based vibration detection system on the machine. The study also includes data collection using the developed vibration detection system. Then, data analysis was done to investigate the trend of the vibrational data. Structured experiments were conducted where 10 samples were printed for each normal and faulty conditions. A vibration motor was attached to the machine when simulating faulty condition printing process. Using the collected vibration data, the analysis showed a strong correlation between vibration and failure of the machine. Several failure predictions were made based on the conducted condition monitoring method where the reading of the of the vibration should be not more than 30 kHz and the average reading should not be more than 5 kHz. The study concluded that the developed vibration detection system is successful in detecting the vibration of the machine during the printing process.